2022
DOI: 10.1002/jcph.2040
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Antiseizure Medication–Induced Severe Cutaneous Adverse Reactions in Malaysia

Abstract: Antiseizure medication can potentially cause severe cutaneous adverse reactions, and certain antiseizure medication‐induced severe cutaneous adverse reactions are associated with specific human leukocyte antigen alleles. This caused a change in antiseizure medication prescribing patterns, which may influence the incidence of antiseizure medication‐induced severe cutaneous adverse reactions. Thus, we aimed to determine the incidence of antiseizure medication‐induced severe cutaneous adverse reactions and its ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…However, this change did not reduce the overall ASM‐induced SCAR burden in Malaysia. On the contrary, we observed a worrisome upward trend of CBZ‐induced SCAR incidence over the years, from 0.75% in 2006 to 1.29% in 2018 (average incidence of 1.1%) 18 . Following the compelling success of HLA‐B*15:02 screening in an academic institute in reducing the CBZ‐induced SJS/TEN significantly (unpublished data), there is an apparent need to revisit the cost‐effectiveness of universal HLA‐B*15:02 screening prior to CBZ use with the latest RWE and a more realistic economic model reflecting the real‐world practice.…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…However, this change did not reduce the overall ASM‐induced SCAR burden in Malaysia. On the contrary, we observed a worrisome upward trend of CBZ‐induced SCAR incidence over the years, from 0.75% in 2006 to 1.29% in 2018 (average incidence of 1.1%) 18 . Following the compelling success of HLA‐B*15:02 screening in an academic institute in reducing the CBZ‐induced SJS/TEN significantly (unpublished data), there is an apparent need to revisit the cost‐effectiveness of universal HLA‐B*15:02 screening prior to CBZ use with the latest RWE and a more realistic economic model reflecting the real‐world practice.…”
Section: Introductioncontrasting
confidence: 61%
“…The current practice was modelled to reflect the change in ASM prescribing patterns owing to the increased awareness among clinicians on the association between HLA‐B*15:02 and CBZ‐induced SJS/TEN, however no routine HLA‐B*15:02 screening prior CBZ initiation was available in practice nationwide. Based on the published national prevalent ASM users in 2016, 18 the relative percentages of the 3 real‐world ASM prescriptions are 60% CBZ, 27% LEV and 13% LTG.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbamazepine was also the most common AED causing SCARs in Hong Kong and Taiwan until the national implementation of HLA-B*15:02 screening policy, which significantly reduced the cases of carbamazepine-induced SCARs reported. 23,24 In a paper calculating incidence rate for carbamazepineinduced SCARs in Malaysia, Fong et al 25 showed that there was a downward trend in carbamazepine-induced SCAR incidence from 2017 to 2019. The trend could be due to the HLA-B*15:02 screening or substitution of carbamazepine with other antiseizure medications whenever the screening is not accessible, as HLA-B*15:02 testing has been available only in selected facilities in the capital, Kuala Lumpur, since 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several drawbacks of a spontaneous reporting system such as underreporting and the lack of a denominator, the cases identified were sufficient to trigger a quantitative signal in our local and international ADR database for carbamazepine‐induced SCARs. In a previous study conducted by Fong et al, 25 using SCAR data from our database and national drug use data, the incidence rate for carbamazepine‐induced SCARs was calculated as an average of 11 per 1000 person‐years. In addition, this analysis was carried out on the basis of voluntary reports without intervention.…”
Section: Discussionmentioning
confidence: 99%